Supporting e-science: scientific research data curation - Vrana, Radovan (Array, 2011)
One of the outcomes of the continuous development of science is creation of new methods of scientific research which, as a result, generate different types of research output including research data. While a significant attention is given to preservation of journal articles, books, and papers published in conference proceeding, less attention is given to the preservation of research data. To enable use of data accumulated in previous scientific research projects in a new scientific research, research data should be preserved. The activity of research data preservation is called data curation. Data curation has become necessary if science wants to avoid data loss. Unfortunately, science itself cannot take care of research data easily ; it needs help from professionals like librarians and archivists to preserve research data in order to enable their re-use future scientific research. Although there are already some good solutions to this problem such as storing research data in digital repositories, no final decision has been made about who will take the responsibility for this kind of activity in the long run.